Amos Paul Kennedy, Jr. - citizen printer - Kennedy, Amos Paul Jr. 1948-; Beasley, Myron M.; Walters, Kelly ca. 20. Jh (Letterform Archive Books, 2024)
"A self-described "humble negro printer," Amos Paul Kennedy, Jr., is internationally recognized for his type-driven messages of social justice and Black power, emblazoned in rhythmically layered and boldly inked prints made for the masses. Borrowing words from civil rights heroes such as Rosa Parks, Fannie Lou Hamer, Frederick Douglass, and Sojourner Truth, Kennedy issues fearless statements on race, capitalism, history, and politics--along with plenty of witty truisms--in his exuberant, colorful, and one-of-a-kind posters and handbills. A vital monograph on a trailblazing contemporary Black artist, Citizen Printer features more than 800 reproductions representing the breadth of Kennedy's letterpress prints (including rarely seen artist's books), plus original portraiture of the maker at work, a powerful manifesto, and a foreword by New York Times bestselling author Austin Kleon, all presented in a dynamic and type-forward design from AIGA medalist Gail Anderson and Joe Newton. With essays by scholars Kelly Walters and Myron M. Beasley, Citizen Printer tells Kennedy's inspiring story and contextualizes his work within the entwined legacies of Black printing and Black protest--and offers readers tools for lifting their voices so they too can agitate, agitate, agitate for a better TODAY." --Publisher's website
Keywords: Kennedy, Amos Paul -- Jr. -- 1948-; Geschichte; Aktivismus; Flugblatt; Politisches Plakat; Schwarze; USA; Kennedy, Amos Paul / Jr; Letterpress printing / Specimens; Letterpress printing / Political aspects; Letterpress printing / Social aspects; Social justice in art; Impression en relief / Spécimens; Impression en relief / Aspect politique; Impression en relief / Aspect social; Justice sociale dans l'art; HISTORY / United States / General; exhibition catalogs; Exhibition catalogs; Backless bindings; Catalogues d'exposition; Bildband